Optimization of differentiated learning through training on innovative learning activities using Loose Parts - Yuniarta Syarifatul Umami; Aisyah Nur Atika (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
The new paradigm of the Merdeka Curriculum emphasizes the implementation of differentiated learning, aiming to provide enjoyable learning experiences tailored to students' knowledge levels and learning needs. This Community Service Program is designed to train early childhood education (PAUD) teachers to adapt and innovate in Differentiated Learning using Loose Parts. The program targets PAUD teachers at the Cluster Activity Center (PKG) in Jelbuk District, Jember Regency. The participating community comprises 17 PAUD institutions, with a total of 30 PAUD teachers involved. The program is conducted in three stages: socialization, training, and best practice mentoring. Methods employed include lectures, quizzes, and project-based activities. Based on participant satisfaction questionnaires, the results of this community service initiative reveal high satisfaction scores: 96.67 percent in the attitude aspect, 90 percent in the knowledge aspect, and 90 percent in the skills aspect. Furthermore, through best practice activities, teachers achieved optimal knowledge and skill transfer. This will enable them to innovate Differentiated Learning activities using Loose Parts, which can be implemented in the learning activities of their respective PAUD institutions.